Revitalization of Social Role Primary Education Teachers in Urban Communities - Latip, Asep Ediana; Rahmaniah, Neli; Wafiqni, Nafia (EDUCARE: Journal of Primary Education, 2023)
This research departs from the problem that the existence of teachers, related to their status and role in society is not always in line with the predicate of the teacher who is attached when teaching at school. Therefore, this study aims: 1) to describe the social role of teachers in urban communities; 2) to describe the relevance of the role of teachers in schools among urban communities; 3) to describe the subjective responses of the surrounding community regarding the role of teachers in urban communities; 4) to describe the revitalization of the role of teachers in urban communities. This research is a case study using a qualitative descriptive approach. The data is collected through questionnaire, interview, and observation methods. Data analysis was carried out in descriptive stages including data reduction, data presentation, and conclusion drawing. This is based on the data analysis model of Miles and Huberman. While testing the validity of the data is by triangulation technique. The research respondents were elementary school primary school teachers in the city of South Tangerang. The results of the study explain that basic education teachers have a social role in South Tangerang urban communities, besides, the social role of basic education teachers is relevant to their role in the South Tangerang urban community, in carrying out their social role, teachers get support from the South Tangerang urban community, as well as revitalization the social role of primary education teachers in the South Tangerang urban community environment is done by time management, organizing performance, and support from the community, as well as strengthening the knowledge of teachers.